When Politics Tipped the Scales: Locating Polish Documentary Films from the 1940s. Issue 4 (2nd October 2018) - Misiak, Anna
Abstract : This article introduces the reader to the 1940s history of the documentary film in post-war Poland when the tense relationship between the Communist government and the small community of documentarians determined the contents of factual cinema. The author argues that the formal and thematic choices made by the 1940s filmmakers fuelled the future growth of the Polish School of Documentary. Despite repressive censorship and close political scrutiny, the 1940s directors produced numerous subjective film visions of the social reality around them. Some worked in line with the political propaganda; others capitalised on the available margins of creative freedom; however, small the latter might appear from today's perspective. Not only do these films testify to an unprecedented early proliferation of authorial creativity among Polish documentary film-makers, but they also form social and political chronicles of their time, a potentially valuable material for the history of everyday life under Communism. As micro-historical film records, they can complement the conventional macro-historical approaches, which with only some exceptions, tend to dominate the Western studies of the world once hidden behind the Iron Curtain.